Spinal Serotonin and 5HT6 Receptor Levels During Development of Neuropathy and Influence of Blockade of these Receptors on Thermal Hyperalgesia in Diabetic Mice - Sari, Cagda Celik; Gunduz, Ozgur; Ulugol, Ahmet (Drug Research, 2019)
Little is known about the role of 5-HT6 receptors in the pathophysiology of neuropathic pain. The aim of this study is firstly, to investigate the influence of spinal and systemic 5-HT6 receptors on thermal hyperalgesia, one of the most significant symptoms of neuropathy occurring in diabetes; and secondly to determine spinal lumbar serotonin and 5-HT6 receptor levels during development of diabetic neuropathy in mice. Diabetes was produced in Balb/c mice with a single injection of streptozocin (150 mg/kg, i.p.). Using the hot plate test, the 5-HT6 antagonist SB-258585 was given systemically (3, 10, 30 mg/kg) and intrathecally (0.01, 0.1, 1 nmol/mouse) to determine its effect on thermal hyperalgesia. Furthermore, on days 7 and 15 of diabetes, development of thermal hyperalgesia was evaluated in relation to changes in spinal serotonin and 5-HT6 receptor levels by using LC/MS/MS and Western blot analyses, respectively. Two-way analysis of variance and unpaired t-tests were used to evaluate data from hot-plate tests and 5-HT levels/ 5-HT6 receptor expression, respectively. Thermal hyperalgesia was observed in neuropathic mice, starting from day 5 after streptozocin administration. On day 15, systemic, but not intrathecal, SB-258585 attenuated thermal hyperalgesia in neuropathic mice. Spinal serotonin levels did not change during development of hyperalgesia after induction of diabetes, whereas spinal 5-HT6 receptor levels were significantly reduced on days 7 and 15. Our findings show that systemic, but not spinal, blockade of 5-HT6 receptors may exert antihyperalgesic effects in neuropathic mice and suggest that systemic 5-HT6 receptors contribute to the pathophysiology of diabetic neuropathy.
Keywords: diabetic neuropathy; neuropathic pain; serotonin; 5-HT6 receptors; thermal hyperalgesia